Research Progress on Plant-based Meat Texturization - Changqi LIU; Yao ZHANG; Zepeng LIU; Jiawei LU; Yanping LI; Yanqin ZHAO; Yuanyong TIAN; Hang LU; Xuefeng LU; Hui ZHAO (Shipin gongye ke-ji)
To satisfy the consumers' nutritional protein needs and achieve sustainable development of food resources, plant-based meat was received extensive attention as an effective alternative to animal meat products. The main component of plant-based meat is plant-derived protein, which is mainly β-sheet in the secondary structure and spherical, different from animal-derived protein with α-helix and linear structure. The development of new plant proteins, the optimization of processing technology, the improvement of sensory characteristics, and the guarantee of nutritional safety are the main challenges facing the future development of plant-based meat products. Combined with the above problems, this paper introduces the source of plant-based meat protein, reviews the technology and principle of plant-based meat organization, analyzes the problems existing in the production of plant-based meat products, and discusses feasible countermeasures, to provide reference for the development of plant-based meat products.